Impact and mechanism of improving the UV aging resistance performance of modified asphalt binder - Zheng Guanghui; Liang Jingqing; Zheng Xuehui; Sun Xiaolong; Xu Hualong (Reviews on Advanced Materials Science)
To control the ultraviolet (UV) aging behavior of asphalt pavement materials effectively, hindered amine light stabilizer (HALS) is preferred as modifiers. The chemical properties of the modifier are systematically studied using infrared spectroscopy experiments. Anti-UV aging-modified asphalt is prepared and subjected to full cycle UV aging treatment using the durability test chamber. The influence of hindered amine light stabilizers on the basic properties of asphalt under UV aging conditions is analyzed. Scanning electron microscope and atomic force microscopy are used to deeply characterize the evolution law of micromorphology of modified asphalt during UV aging. The composition and variation of functional groups in UV-aged-modified asphalt are studied using the Fourier transform infrared spectroscopy system. The research results indicate that the addition of HALS could increase the penetration and ductility of asphalt and the increasing effect could reach 29 and 35%. When subjected to UV radiation, the maximum improving effect of HALS could reach above 50%. Hindered amine light stabilizers could react with asphalt materials and cause aromatization changes in asphalt components. The typical functional group indices of asphalt decreased by 90% approximately. Under the action of ultraviolet radiation, the modified asphalt could show good antiaging performance and could inhibit the aging behavior of the 70# asphalt and the deterioration of road performance.